Haptoglobin groups in motor neuron disease. Issue 3 (March 1988) - Fröhlander, N; Forsgren, L
Abstract : Haptoglobin (Hp) groups were investigated in 81 patients with motor neuron disease. A significant excess of heterozygotes was observed, accentuated among males and in the progressive spinal muscular atrophy subgroup. The results are discussed in terms of a possible influence of Hp in the immunological response.